Female Resistance on Domestic Violence in Nathaniel Hawthorne’s Wakefield - Agung Suhadi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research presents the study of female resistance on domestic violence in Nathaniel Hawthorne’s Wakefield. In this story, Hawthorne plays the female character who undergoes the form of domestic abuse within the family institution. His voice visible misogynistically, the female-oppressed is not only for keeping an authority, but also due to the failure to manage his marriage. In this study, the textual analysis is employed to explore the forms of domestic abuse by conducting close-reading (in-depth), identifying, grouping, and interpreting the related-words/clues/quotation of domestic violence on female. The results of analysis demonstrate that self-reliance of female character as vividly described by Hawthorne becomes a way of his female to fight against the domestic violence by male. In shorts, through his story, Hawthorne boldly enforces his female character triumphant as a way for resistance toward violence around her life. Keywords: violence, domestic, self-reliance, female, short story